Optimization Of VCO (Virgin Coconut Oil) Development As A Local Product At UMKM Dua Puteri In Abbokkongang Village, Sidrap Regency - Hasdiana Hasdiana; Arfianty Arfianty; Sukmawati Thasim; Indira Cahyani; Rismawati N; Della Rahmawati Irwan (International Journal Of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the regional economy, including improving community welfare through the development of local products. One potential product that can be developed is Virgin Coconut Oil (VCO), which has high economic value and extensive health benefits. UMKM Dua Puteri in Abbokkongang Village, Sidrap Regency, is one of the businesses focused on VCO production. However, it still faces various challenges, such as production efficiency, marketing, and business management.This Student Creativity Program (PKM) aims to optimize the development of VCO as a local product by enhancing production capacity, implementing quality standards, and adopting more effective marketing strategies. The methods used include technical training on VCO processing, mentoring in production standard implementation, and digital marketing to expand market reach. Through this optimization, UMKM Dua Puteri is expected to improve its product competitiveness, expand its marketing network, and contribute to the economic growth of the Abbokkongang Village community.